Mature B cells accelerate wound healing after acute and chronic diabetic skin lesions. Issue 5 (17th October 2017) - Sîrbulescu, Ruxandra F.; Boehm, Chloe K.; Soon, Erin; Wilks, Moses Q.; Ilieş, Iulian; Yuan, Hushan; Maxner, Ben; Chronos, Nicolas; Kaittanis, Charalambos; Normandin, Marc D.; El Fakhri, Georges; Orgill, Dennis P.; et al.
Abstract: Chronic wounds affect 12–15% of patients with diabetes and are associated with a drastic decrease in their quality of life. Here, we demonstrate that purified mature naive B220 + /CD19 + /IgM + /IgD + B cells improve healing of acute and diabetic murine wounds after a single topical application. B cell treatment significantly accelerated acute wound closure by 2–3 days in wild‐type mice and 5–6 days in obese diabetic mice. The treatment led to full closure in 43% of chronic diabetic wounds, as compared to only 5% in saline‐treated controls. Applying equivalent numbers of T cells or disrupted B cells failed to reproduce these effects, indicating that live B cells mediated pro‐healing responses. Topically applied B cell treatment was associated with significantly reduced scar size, increased collagen deposition and maturation, enhanced angiogenesis, and increased nerve growth into and under the healing wound. β‐III tubulin+ nerve endings in scars of wounds treated acutely with B cells showed increased relative expression of growth‐associated protein 43. The improved healing associated with B cell treatment was supported by significantly increased fibroblast proliferation and decreased apoptosis in the wound bed and edges, altered kinetics of neutrophil infiltration, as well as an increase in TGF‐β and a significant reduction in MMP2 expression in wound granulation tissue. Our findings indicate that the timeline and efficacy of wound healing can be experimentally manipulated through the direct application of mature, naive B cells, which effectively modify the balance of mature immune cell populations within the wound microenvironment and accelerate the healing process.